2012
DOI: 10.1134/s0006297912040050
|View full text |Cite
|
Sign up to set email alerts
|

Influence of centrin 2 on the interaction of nucleotide excision repair factors with damaged DNA

Abstract: We have examined the influence of centrin 2 (Cen2) on the interaction of nucleotide excision repair factors (XPC-HR23b, RPA, and XPA) with 48-mer DNA duplexes bearing the dUMP derivative 5-{3-[6-(carboxyamidofluoresceinyl)amidocapromoyl]allyl}-2'-deoxyuridine-5'-monophosphate. The fluorescein residue linked to the nucleotide base imitates a bulky lesion of DNA. Cen2 stimulated the binding and increased the yield of DNA adducts with XPC-HR23b, a protein recognizing bulky damages in DNA. Stimulation of the bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…XPC functions as a heterotrimer with HR23B and centrin-2, which stimulate XPC DNA binding activity and increases cellular stability 49 . Once engaged on the damaged duplex, XPC recruits the TFIIH complex 43 .…”
Section: Xpa Interaction With Other Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…XPC functions as a heterotrimer with HR23B and centrin-2, which stimulate XPC DNA binding activity and increases cellular stability 49 . Once engaged on the damaged duplex, XPC recruits the TFIIH complex 43 .…”
Section: Xpa Interaction With Other Proteinsmentioning
confidence: 99%
“…XPA (and RPA) was originally thought to contribute to damage recognition and verification, in part due to its interaction with XPC. However, more recent experiments showed that XPA (in concert with RPA) is recruited to the damaged site after the formation of the NER bubble 49 .…”
Section: Xpa Interaction With Other Proteinsmentioning
confidence: 99%
“…Centrin2 co-fractionates with xeroderma pigmentosum group C protein (XPC) and its interactor, HRAD23B, key proteins that direct the initial DNA damage recognition step of an NER pathway termed global genome repair [31,32]. The role played by centrin2 in NER is unclear: in vitro NER can be carried out in its absence, although it increases NER activity somewhat [3235]. Nevertheless, centrin2 moves to the nucleus after UV irradiation in an XPC-dependent manner and is required for efficient repair of UV-induced DNA lesions in both human and chicken cells [25,36].…”
Section: Introductionmentioning
confidence: 99%
“…XPC functions in GG-NER within the XPC-RAD23B-CETN2 complex; the interaction of XPC and RAD23B has been shown to increase the affinity of XPC for damaged DNA [8] while the interaction between XPC and CETN2 has been shown to stabilize XPC and promote NER [1,9]. The interactions of XPC with CETN2, RAD23B, and XPA have been biochemically characterized [10,11].…”
Section: Introductionmentioning
confidence: 99%